Task type's effect on attitudes towards voice assistants - Sung, Billy; Im, Hyunjoo; Duong, Van Chien (International journal of consumer studies, 2023)
There is an emerging interest in examining user attitudes towards voice assistants (VAs); however, there is limited research on how user attitudes are formulated in different contexts. Drawing from the stereotype content models, the current study attempts to investigate how users perceive and evaluate voice assistants (VAs) in different contexts (i.e., functional vs. social tasks) based on warmth, competence and trustworthiness. Study 1 (N = 123) employs a within‐subjects design to examine how task type (functional vs. social) affects user perceptions and attitudes towards a VA (i.e., Google Assistant). Study 2 (N = 116) and Study 3 (N = 61) examine the boundary effect of perceived psychological power and ease of use. The findings show that attitude is significantly more positive in functional tasks (vs. social), and this effect is mediated by perceived competence. This indirect effect is also significantly moderated by perceived ease of use. Perceived warmth does not mediate the effect of social tasks on attitude, and trust in VAs is a direct outcome of functional tasks. Taken together, this study contributes to both theory and practice in many ways. Specifically, the findings are the first to demonstrate a direct effect of task type on consumer perceptions and attitudes. Additionally, the findings indicate that user evaluations of VAs are still dominated by user perceptions of the competence of the VAs.